Macromol. Rapid Commun. 11/2016. Issue 11 (June 2016) - Bagheri, Ali; Yeow, Jonathan; Arandiyan, Hamidreza; Xu, Jiangtao; Boyer, Cyrille; Lim, May
Abstract : Back Cover: Polymers featuring photoresponsive groups have been exploited as promising drug delivery systems. Light as spatially and temporally controllable external stimulus can be readily tuned and focused to trigger changes in the structure of polymer chains to provide "on‐command" drug delivery. A benign synthesis route for a novel controlled polymerization, known as photoinduced electron/energy transfer–reversible addition–fragmentation (PET‐RAFT) polymerization, is presented. Further details can be found in the article by A. Bagheri, J. Yeow, H. Arandiyan, J. Xu, C. Boyer, * and M. Limon page 905.